Ecological features of a freshwater stream near pechipparai reservoir, Kanyakumari district - Prateek; S. David Kingston; T. Francis (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The prime objective of the study was to analyze the ecological features and to identify the fish species present along the upstream region of Pechipparai reservoir. Seventeen species of freshwater fishes belonging to 11 genera and 8 families have been recorded. Cyprinidae was the dominant family (6 species) in the study area. Of the 17 species, Dawkinsia arulius belong to the endangered category, Hyporhamphus xanthopterus and Dawkinsia rohani to vulnerable and Ompok bimaculatus to near threatened category. All the 17 fish species are found to be endemic to India and ornamentally appreciated.